Studies on preparation of mixed fruit toffee from Fig and Guava fruits - Kohinkar, S. N. (Springer India, 2012)
Studies were carried out to develop a technology for preparation of mixed fruit toffee from fig and guava fruit pulp and to evaluate the changes in quality of prepared toffees during storage under ambient as well as refrigerated conditions for 180 days. Among the various combinations of fig and guava fruit pulp, toffee prepared from75:25 w/w (fig: guava) ratios was found better than other combinations in respect to yield, organoleptic properties and nutritional quality. The cost of toffee prepared from higher level of fig pulp i.e. 75:25 (fig:guava) ratio was higher (Rs. 71.84/kg). The storage studies of toffees packed in 200 gauge polyethylene bags indicated that the TSS, reducing and total sugars increased with the advancement of storage period, while moisture and acidity content decreased. The rate of reactions was relatively higher at ambient temperature than refrigerated temperature. Though the sensory quality of toffees also decreased at faster rate during 180 days storage period at ambient condition than the refrigerated condition yet the toffees were found to be acceptable even after 180 days at both the conditions.